Layer-by-layer assembled heteroatom-doped graphene films with ultrahigh volumetric capacitance and rate capability for micro-supercapacitors - Wu, Zhong-Shuai; Parvez, Khaled; Winter, Andreas; Vieker, Henning; Liu, Xianjie; Han, Sheng; Turchanin, Andrey; Feng, Xinliang; Muellen, Klaus (Advanced Materials, 2014)
Highly uniform, ultrathin, layer-by-layer heteroatom (N, B) co-doped graphene films are fabricated for high-performance on-chip planar micro-supercapacitors with an ultrahigh volumetric capacitance of ¢ 488 F cm-3 and excellent rate capability due to the synergistic effect of nitrogen and boron co-doping. © 2014 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.
CRIS-Team Scopus Importer:2023-03-20
Keywords: energy storage; graphene film; heteroatom doping; layer-by-layer self-assembly; micro-supercapacitors